Tailoring of unipolar strain in lead-free piezoelectrics using the ceramic/ceramic composite approach - Khansur, Neamul H.; Groh, Claudia; Jo, Wook; Reinhard, Christina; Kimpton, Justin A.; Webber, Kyle Grant; Daniels, John E.; Khansur, Neamul Hayet (Journal of Applied Physics, 2014)
The electric-field-induced strain response mechanism in a polycrystalline ceramic/ceramic composite of relaxor and ferroelectric materials has been studied using in situ high-energy x-ray diffraction. The addition of ferroelectric phase material in the relaxor matrix has produced a system where a small volume fraction behaves independently of the bulk under an applied electric field. Inter- and intra-grain models of the strain mechanism in the composite material consistent with the diffraction data have been proposed. The results show that such ceramic/ceramic composite microstructure has the potential for tailoring properties of future piezoelectric materials over a wider range than is possible in uniform compositions. (C) 2014 AIP Publishing LLC.